Cumulative Burden of Illness in Veterans With Tardive Dyskinesia and Serious Mental Disorders. Issue 1 (January 2020) - Caroff, Stanley N.; Leong, Shirley H.; Roberts, Christopher; Berkowitz, Rosalind M.; Campbell, E. Cabrina
Abstract: Purpose/Background: To inform cost-benefit decisions for veterans, the risk of tardive dyskinesia (TD) and its impact on comorbidities and outcomes were assessed. Methods/Procedures: In a retrospective study, veterans with schizophrenia/schizoaffective, and bipolar and major depressive disorders receiving antipsychotics during the period October 1, 2014, to September 30, 2015, were identified. Tardive dyskinesia was determined by International Classification of Diseases, Ninth Revision, Clinical Modification codes. Correlates of TD were examined using χ 2 or t tests. Odds ratios (ORs) and β parameters with 95% confidence intervals (CIs) for categorical and continuous variables associated with TD were derived from a multivariate logistic and linear regression, respectively. Findings/Results: Among 7985 veterans, 332 (4.2%) were diagnosed as having possible TD. The odds of having TD were higher for older veterans (OR, 1.04; 95% CI, 1.03–1.05; P < 0.0001) and veterans with schizophrenia/schizoaffective disorder (OR, 1.54; 95% CI, 1.23–1.91; P < 0.0001) or diabetes (OR, 1.64; 95% CI, 1.30–2.06; P < 0.0001). Veterans with TD received more antipsychotic prescriptions (mean ± SD, 18.4 ± 30.3 vs 13.3 ± 26.4; P = 0.003) and days of supply (233.9 ± 95.4 vs 211.4 ± 102.0; P < 0.0001). They were more likely to have received 2 or more antipsychotics (27.1% vs 19.7%, P = 0.0009) and benztropine (OR, 2.25: 95% CI 1.73–2.91; P < 0.0001). Veterans with TD had a higher Charlson Comorbidity Index score (β = 0.32; SE, 0.09; 95% CI, 0.14–0.49; P = 0.0003) and higher odds of any medical hospitalization (OR, 1.45; 95% CI, 1.07–1.95; P = 0.001). Implications/Conclusions: The diagnosis of possible TD was associated with older age, schizophrenia/schizoaffective disorder, medical comorbidity, and hospitalization. Tardive dyskinesia may be a marker for patients at risk of adverse health care outcomes and diminished quality of life. Abstract : Supplemental digital content is available in the text.